2014
DOI: 10.1590/s0100-204x2014001100003
|View full text |Cite
|
Sign up to set email alerts
|

Monitoramento do percevejo marrom Euschistus heros (Hemiptera: Pentatomidae) por feromônio sexual em lavoura de soja

Abstract: Resumo -O objetivo deste trabalho foi avaliar a eficiência das formulações septo de borracha e lure do feromônio sexual do percevejo marrom Euschistus heros e compará-la ao método do pano de batida, para o monitoramento dessa praga em lavoura de soja. Os tratamentos foram: feromônio em septo de borracha, feromônio em lure e amostragem com pano de batida. As amostragens foram realizadas semanalmente durante a fase reprodutiva da soja (dez semanas). Para estimar a densidade populacional de percevejos e compará-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
1
2
0
2
Order By: Relevance
“…The temporal variation of adults was in line with Silva et al (2014), who found the stabilization of adult growth when the plants were at the grain filling stage (R5 to R5.4).…”
Section: Temporal Variation Of E Herossupporting
confidence: 85%
See 1 more Smart Citation
“…The temporal variation of adults was in line with Silva et al (2014), who found the stabilization of adult growth when the plants were at the grain filling stage (R5 to R5.4).…”
Section: Temporal Variation Of E Herossupporting
confidence: 85%
“…The nymph population grew throughout the evaluations, surpassing the number of adults when the soybean was at R6 (Figure 1), a moment characterized by full and green grains. This fact is corroborated by Silva et al (2014), who observed an increase in the number of nymphs after the grain formation and filling period, which may be explained by the appearance of pods, making soybean more nutritionally suitable for reproduction, and increasing the number of nymphs (Fonseca et al, 2017).…”
Section: Temporal Variation Of E Herosmentioning
confidence: 64%
“…Sampling defines the population of insects present in a particular area of cultivation, being a presupposition for decision making under the precepts of Integrated Pest Management (Guedes et al, 2006;Riffel et al, 2012). Different techniques to know the population of a certain species of insect-plague or natural enemy are spent by technical assistants and producers, the most known and used are: direct observation, pinworm, entomological net, light trap and sexual pheromone trap (Silva et al, 2014;Pasini et al, 2015;Storck et al, 2016;Garlet et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Para fazer um bom monitoramento é recomendado fazer amostragens semanalmente desde os estágios vegetativos até o reprodutivo da lavoura, com atenção ao desenvolvimento das sementes, pois é a fase de maior densidade populacional do percevejo (SILVA et al, 2014).…”
Section: Monitoramentounclassified
“…O tecido é colocado no solo e as plantas são sacudidas vigorosamente para que os percevejos caiam nele e assim fazer a contagem de adultos e das ninfas grandes. Este tipo de monitoramento é geralmente realizado durante o período sintético, as quais são instaladas no perímetro da lavoura para capturar os percevejos e realizar a contagem(SILVA et al, 2014). A vantagem desse método é que por serem compostos naturais, eles não representam risco para o meio ambiente nem para os seres humanos, permitem uma detecção rápida da praga e não geram resistência aos percevejos (…”
unclassified